From the parlour to the kitchen: a study of the transformative potential for further education teachers of continuing professional development - Scott, Alison Elizabeth (2017)
A pervasive audit culture within English Further Education (FE) Colleges from 1992 has meant that the content of continuous professional development (CPD) for further education (FE) teachers has been largely determined by the themes and concerns of inspection. Viewed through the lens of Jürgen Habermas’s theory of ‘communicative action’, it is argued that FE teachers’ practice has been dominated by external and internal structural constraints, exacerbated by the workings of hegemony by which teachers have been made complicit. It is shown that audit-driven management practices have focussed on an instrumental approach to CPD, developing teachers’ performative skills and neglecting more embedded improvements to practice. My starting premise was that this trend could be understood using the Habermasian term, ‘colonisation of the lifeworld’; this premise is reflected in FE literature where the compromised agency of teachers is the dominant discourse. The fieldwork identified the key constraints and enablers in maintaining teachers’ lifeworld and the possibilities for developing empowering forms of CPD to overcome victimhood and re-invigorate professionalism. Qualitative data was generated by interviews with seventeen teachers and one focus group within one large FE College. The key finding is that CPD could be used as a site for what Habermas terms ‘ideal speech conditions’: Habermas’s theory of communicative action is used to support the argument that CPD’s transformative impact is realised if teachers engage in authentic discussions about practice and are empowered to determine their own practice change.